Trends in Mycotoxins Co-Occurrence in the Complete Feed for Farm Animals in Southern Romania During 2021–2024 Period - Valeria Cristina Bulgaru; Mihail Alexandru Gras; Aglaia Popa; Gina Cecilia Pistol; Ionelia Taranu; Daniela Eliza Marin (Toxins)
Mycotoxins are common natural contaminants of crops and fruits, associated with negative effects on human and animal health. Currently, more than 300 mycotoxins have been identified, but data on their effects and their limits in feed and food are still inconsistent. The European Commission, by directive EC 574/2011, established regulations concerning the maximum limit allowed in farm animals’ feed for aflatoxins, but for all other mycotoxins there are only recommendations (EC 1319/2016) and there are no established limits. Considering their variety and toxic effects, but also the fact that not many details are yet known about the cumulative effects of co-contamination with various mycotoxins, it is necessary to monitor the evolution of their presence in animal feed. The aim of our study was to analyze for a four-year period (2021–2024) the concentrations of six mycotoxins (total aflatoxins-AFT, fumonisins-FB, deoxynivalenol-DON, zearalenone-ZEA, T2/HT2 and ochratoxin (A + B)-OTA), the most frequently encountered in the south area of Romania in poultry, piglets and pig’s complete feed. Our results showed that the maximum highest concentrations were 5.8 ppb for AFT, 4.7 ppm for FB, 1.9 ppm for DON, 62.8 ppb for ZEA, 32.1 ppb for T2/HT2 and 19.7 ppb for OTA irrespective of the type of feed. It should be noted that AFT and ZEA were identified in all samples during the entire monitored period, and the only mycotoxin that exceeded the guidance value was DON, for which the recommendation of 0.9 ppm for pig feed was exceeded. Recent studies demonstrated that sub-chronic and chronic exposure to low concentrations of mycotoxins and specially co-contamination is more common than acute exposure, being able to affect animal health over time by lowering the defense capacity, inducing inflammatory reactions and affecting intestinal health, which in the long term could have important economic consequences. Our survey study can provide important data showing the degree of contamination with mycotoxins in pig and poultry feed including the simultaneous presence of different mycotoxins in this complete feed.